THE INFLUENCE OF COSSACKS’ ETHOS ON THE PHILOSOPHY OF H.SKOVORODA - Матюхіна, О. А. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
Тhe article is dedicated to the analysis of Cossacks’ ethos and its influence on H. Skovoroda’s philosophy.